The Nature-based Tourism Sustainability: Cultural Measures and Personality Trait - Ali Imron; Siti Nurhayati; Nur Choirul Afif (Qubahan Academic Journal)
A tourism that relied on nature-based tourism (NBT) was not enough as a reason for revisit intention. Revisit intention are the key of tourism sustainability. This study aim to determine cultural background as personalities of tourism destination. The objectives are to justify the tourism destination culture personality relevant for destination personality measurement which seen from culture perspective. Through destination personality approach, this study investigates the role of tourism destination culture personality to strengthen the effect of tourist engagement and memorable tourism experience which can lead to a higher revisit intention considering the match between destination image and tourist’s self-concept. Tourism destination culture personality is a concept that integrates the concepts of destination personality and Hofstede's dimension of culture to describe the unique cultural identity of a tourism destination. In this matter, 259 respondents from a single nation was involved to evaluate 15 scale items of tourism destination culture personality and the framework of current research. Results show that all scale items of tourism destination culture personality were valid. The SEM-PLS and The importance-performance map analysis (IPMA) justified that tourism destination culture personality is essential concept for optimizing the relationship between tourist engagement and memorable tourism experience on revisit intention. Moreover, the tourism destination culture personality has È-Shape curvilinear relationship on the tourist engagement and revisit intention which projected. The last, these results were assessed by robustness and configuration tests to reduce the possibility of error regarding our findings. Overall, this study contributes to the extant literature on tourism destination culture-personality by constructing a composite picture of tourism destination culture-personality dimensions on the tourist’ engagement, memorable tourism experience and revisit intention of NBT. The study’s theoretical contributions, its restrictions and practical implications for NBT operators are further discussed.